PENGARUH KADAR HORMON BASAL TERHADAPJUMLAH OOSIT MATUR PADA PASIEN PROGRAM IVF-ICSI TAHUN 2006-2010 DI RSUP DR SARDJITO - , Nilawati ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Follicle Stimulating Hormone initiates follicular growth and stimulates the development of Graafian Follicle. During this process, the increase of estrogen synthesis stimulates secretion of LH and ovulation occurs. This hormone is very important in predicting successfulness of in vitro fertilization program. Objective: To analyze the relation of basal hormone levels (FSH, LH, and E2) in predicting the total number of mature oocyte in patients following IVF-ICSI program. Methods: Observational retrospective cohort. Results: A total of 60 cycles from 60 couples who undergoing IVF were included in the study according to inclusion and exclusion criteria. There were 16 cyles (26.7%) with normal basal hormon level (FSH â¤ 7.5 mIU / mL, E2 â¤ 50 pg / mL, LH â¤ 4 mIU / mL) and 44 cycles (73.3%) with abnormal basal hormone levels. Twenty subjects (33%) using ovarian stimulation long protocol rFSH and GnRH agonist, 15 subyek (23%) with combination of ovarium Clomiphene Citrate and rFSH (simple protocol) and 25 subjects (41.7%) with GnRH antagonis protocol. Normal basal hormone increase the chance by 2.1 fold in producing mature oocyte. Basal FSH â¤ 7.5 mIU / mL significantly increase the amount of mature oocyte compare to basal FSH > 7.5 mIU / mL (7.59Â±4.9 vs 5.38Â±2.7